Effect of exercise training on cardiac mitochondrial respiration, biogenesis, dynamics, and mitophagy in ischemic heart disease - Viloria, Mary Audrey D.; Li, Qing; Lu, Wang; Nhu, Nguyen Thanh; Liu, Yijie; Cui, Zhen-Yang; Cheng, Yu-Jung; Lee, Shin-Da (Frontiers in Cardiovascular Medicine, 2022)
Objective Cardiac mitochondrial dysfunction was found in ischemic heart disease (IHD). Hence, this study determined the effects of exercise training (ET) on cardiac mitochondrial respiration and cardiac mitochondrial quality control in IHD. Methods A narrative synthesis was conducted after searching animal studies written in English in three databases (PubMed, Web of Science, and EMBASE) until December 2020. Studies that used aerobic exercise as an intervention for at least 3 weeks and had at least normal, negative (sedentary IHD), and positive (exercise-trained IHD) groups were included. The CAMARADES checklist was used to check the quality of the included studies. Results The 10 included studies (CAMARADES score: 6–7/10) used swimming or treadmill exercise for 3–8 weeks. Seven studies showed that ET ameliorated cardiac mitochondrial respiratory function as manifested by decreased reactive oxygen species (ROS) production and increased complexes I-V activity, superoxide dismutase 2 (SOD2), respiratory control ratio (RCR), NADH dehydrogenase subunits 1 and 6 (ND1/6), Cytochrome B (CytB), and adenosine triphosphate (ATP) production. Ten studies showed that ET improved cardiac mitochondrial quality control in IHD as manifested by enhanced and/or controlled mitochondrial biogenesis, dynamics, and mitophagy. Four other studies showed that ET resulted in better cardiac mitochondrial physiological characteristics. Conclusion Exercise training could improve cardiac mitochondrial functions, including respiration, biogenesis, dynamics, and mitophagy in IHD. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=226817, identifier: CRD42021226817.